Em busca de um conselho... A experiência de uma etnografia urbana na região do Nordeste de Amaralina - VILELA, Vandré Almeida de Carvalho (2016)
The aim of this study is to analyze the Council of Popular Culture in the Northeast of Amaralina Region (CONCULT) located in Salvador, State of Bahia, in relation to work in the community, implications and limitations. This is an thesis that discusses the issue of the Council's activities through benchmarks topics, such as the discussion about the concepts of slums and peripheries and community and belonging. The study also makes a historical survey and a brief characterization of the Northeast Region of Amaralina and the beginning of community organization in the region and the establishment of the Council of Popular Culture. This research of ethnographic nature obtained as a data collection instrument a structured interview with Councilors of the Concult and, after data analysis allowed to judge on the performance of a Council of Culture in a popular neighborhood, as well as the limitations and perspectives faced by the institution, In order to guarantee the continuity of the actions of art and culture developed in the Region, minimizing social problems faced daily by its residents. This worked opportunized to discuss a segment that is about Councils of Culture (Council of Popular Culture) whose bibliography and studies are still incipient. In this sense, it was also fundamental for the community, since the local population will have a scientific study about the actions undertaken by this Council.